Utilization and optimization of industrial bottom ash for palm oil mill effluent decolourization - Mohammad Saleh, Syahin (2019)
The increasing demand of crude palm oil (CPO) has resulted in the enormous increases in palm oil mills operation in Malaysia and hence the palm oil mill effluent (POME) discharges. Thus, existing treatment facilities have difficulties to comply the discharge limit for this excess POME from the running plants. In this case, colour of POME was one of the major concerns as it will be incorporated in the current regulation. Various adsorbents (i.e POMBA, treated POMBA, CBA, treated PKS) had been screened for POME decolourization. Coal bottom ash (CBA) showed highest colour removal percentage among others and hence selected for the consequence investigations. The raw CBA were then chemically (ACBA) and physically treated (PCBA) for comparison study. Furthermore, response surface methodology (RSM) was used for optimization. As results, the optimum parameters of ACBA and PCBA for POME colour adsorption proposed the followings: 14.20 hr and 15.37 hr contact time, 13.16 g and 13.84 g adsorbent dosage, 27.97% and 57.52% POME concentration, pH 6.24 and pH 6.04, respectively. Both predicted and experimental percentage removal of POME colour for ACBA and PCBA were significantly correlated with the R² values for ACBA and PCBA were 0.9793 and 0.9755, respectively. Physico-chemical characterizations of both treated CBA were performed using BET for surface area, FTIR for its surface chemistry, SEM for morphology and EDX for elemental analysis. It was shown that the isotherms for adsorption of colour from POME onto treated CBA were well fitted by Freundlich model. Furthermore, pseudo-second order was identified to be governing mechanism for both treated CBA. Other pollutants i.e COD, BOD3 and NH3-N removal are also evaluated. It was found that percentage removal of COD, BOD3 and NH3-N using ACBA were 61.33%, 58.33% and 61.43%, respectively. Meanwhile, percentage removal of COD, BOD3 and NH3-N using PCBA were 38.39%, 33.33% and 31.10%, respectively. Upon these findings, CBA has potential not only in POME decolourization also in POME treatment as adsorbent.